IL-6 signaling by STAT3 participates in the change from hyperplasia to neoplasia in NRP-152 and NRP-154 rat prostatic epithelial cells - Barton, Beverly E (BioMed Central, 2001)
BACKGROUND: STAT3 phosphorylation is associated with the neoplastic state in many types of cancer, including prostate cancer. We investigated the role of IL-6 signaling and phosphorylation of STAT3 in 2 rat prostatic epithelial lines. NRP-152 and NRP-154 cells were derived from the same rat prostate, yet the NRP-152 cells are not tumorigenic while the NRP-154 cells are tumorigenic. These lines are believed to represent 2 of the stages in the development of prostate cancer, hyperplasia and neoplasia. Differences in signaling pathways should play a role in the 2 phenotypes, hyperplastic and neoplastic. METHODS: We looked at the phosphorylation state of STAT3 by intracellular flow cytometry, using phospho-specific antibodies to STAT3. We used the same method to examine IL-6 production by the cell lines. We also measured apoptosis by binding of fluorescent annexin V to the cells. RESULTS: Although both cells lines made IL-6 constitutively, phosphorylated-STAT3 was present in untreated NRP-154 cells, but not in NRP-152 cells. Treatment with dexamethasone inhibited the IL-6 production of NRP-152 cells, but enhanced that of NRP-154 cells. Treatment with the JAK2 inhibitor AG490 induced apoptosis in NRP-152, but not NRP-154 cells. CONCLUSIONS: We conclude from these experiments that STAT3 activity plays a role in the phenotype of NRP-154 cell, but not NRP-152 cells. The significance of alternative IL-6 signaling pathways in the different phenotypes of the 2 cell lines is discussed.